EFL learners' challenges to speak English in online speaking classes - Abrar, Mukhlash; Fajaryani, Nunung; Masbirorotni, Masbirorotni; Gustin, Resi Amalia; Ningsih, Ananda Wahyu (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2024)
The purposes of this qualitative inquiry were to explore EFL learners' challenges in online speaking and their strategies in overcoming the challenges. To collect the data, we employed semi-structured interviews and audio diary to 12 EFL learners who voluntarily participated in our study. Based on data analysis, we identified four interrelated themes and sub-themes about EFL learners' challenges in online speaking classes, such as 1) internet and technology related issues (poor connection and lack of technological knowledge); 2) linguistics issues (limited vocabulary, lack of grammatical knowledge, fluency problem, and pronunciation problem); 3) psychological issues (anxiety, low motivation and insecure); and 4 learning proponents (lack of topical knowledge and unsupportive peers). To overcome those encountered challenges, EFL learners used several strategies, including 1) Self-management (self-practice and being well-prepared); 2) helping from others (asking or having discussion with friends and asking the lecturers); and technological support (taking advantage of entertainment platforms and language applications).